2008
DOI: 10.1016/j.bone.2008.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Fracture prevalence and relationship to endocrinopathy in iron overloaded patients with sickle cell disease and thalassemia

Abstract: Transfusional iron overload leads to gonadal failure and low bone mass in patients with thalassemia (Thal). However, gonadal failure is rarely reported in transfused patients with sickle cell disease (SCD) and the literature regarding fracture prevalence in SCD is limited. The objective of this study was to assess self-reported fracture prevalence and its relationship to endocrinopathy in transfused Thal or SCD subjects and compare to non-transfused subjects with SCD (NonTxSCD). Eligibility was based on age ≥1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 30 publications
2
38
0
1
Order By: Relevance
“…Increased serum ferritin has been reported as associated with fractures and decreased bone mass in some studies. 12,19 Serum ferritin levels have been thought to reflect the body iron stores; however, it is also a secreted by-product of intracellular ferritin synthesis. 20 This last process is increased in some inflammation states as chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased serum ferritin has been reported as associated with fractures and decreased bone mass in some studies. 12,19 Serum ferritin levels have been thought to reflect the body iron stores; however, it is also a secreted by-product of intracellular ferritin synthesis. 20 This last process is increased in some inflammation states as chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Fung et al reported that for serum ferritin levels over 2000 ng/ml subjects with more blood transfusions had a greater fracture risk which could be due to iron overload. 12 Nevertheless, the presence of inflammatory proteins such as IL7 has been linked to bone loss, and the high serum ferritin levels could be a marker of chronic inflammation. 20 No matter the main explanation, in this study the serum ferritin levels were higher in subjects with osteopenia/osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yakın zamandaki terapötik yaklaşımlarla talasemili hastalardaki yaşam süresi ve kalitesi artmış, bununla birlikte patolojik kırıklara sebep olabilen osteoporoz, hastalığın en önemli iskelet bulgusu ve morbidite sebebi haline gelmiştir (5,6). İyi tedavi edilen talasemi majörlü hastalarda bile osteoporoz prevalansının %40-50 (3,5), kırık prevalansının %38-41 olduğu bildirilmiştir (7,8). Bu çalışma da hastanemizde düzenli olarak takip ve tedavi edilen TM'li çocuk hastaların kemik sağlığının biyokimyasal parametreler ve kemik mineral yoğunluğu (KMY) ölçülerek değerlendirilmesi, gelişebilecek osteoporoz yönünden erken tanı ve önleyici tedbirlerin alınmasının vurgulanması amaçlandı.…”
Section: Introductionunclassified
“…Osteopenia and osteoporosis are associated with sickle cell disease [20][21][22][23][24] . Iron overload has been correlated with this complication [20,21,25] and the explanation for this might be the inhibition of osteoblast proliferation and differentiation by iron [26] .…”
mentioning
confidence: 99%